(untitled) (Journal for Studies in Humanities and Social Sciences, 2015)
From a policy perspective, the most useful information about child mortality is its determinants. Hence, during the 20th and 21st centuries, researchers have increasingly turned their attention to identifying factors associated with low child mortality in developing countries. The identification of factors that account for variations in childhood mortality is essential in the formulation of policies and programs that aim to reduce child mortality. This paper analyses and compares the determinants of child mortality in Namibia, nationally, and in the two rural regional health directorates (RHDs), namely the Northeast and Northwest, using the 2006-07 Namibia Demographic and Health Survey. The Cox proportional hazard model is applied to assess the relative effects of the independent variables on child mortality. The results show that short birth intervals and widowed or divorced mothers had the highest risk of child mortality (p < 0.001) in Namibia as a whole as well as in the two rural RHDs. Whilst the variables of a toilet facility and mothers’ education showed significance in both the Northeast and Northwest RHDs, their risks were lower in the Northwest. The variation by the sex of the household head only had a distinct impact in the Northeast RHD. These findings support policy initiatives that encourage longer birth intervals via the strengthening of contraceptive use through broader programs of sexual and reproductive health. The results of this study are also expected to guide policy makers and programme managers in the health sector to formulate targeted intervention programs to reduce child mortality in the rural regions of Namibia.